2023
DOI: 10.1039/d2ya00315e
|View full text |Cite
|
Sign up to set email alerts
|

Manganese and selenium co-doped CeO2@Co3O4 porous core–shell nanospheres for enhanced oxygen evolution reactions

Abstract: As one of the semi-reactions of water splitting, electrocatalytic oxygen evolution reaction (OER) is a key process to generate sustainable energy. Co-based spinel oxides are deemed as promising OER electrocatalysts,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
0
4
1
Order By: Relevance
“…When the reaction was extended to 3–6 h, the CoFe-SUCS structure remained almost the same morphology of the sea urchin-like hollow core–shell nanosphere, which is completely different from that of Co-CDSAAs (Figures f–i and S2f–i). Fourier transform infrared (FT-IR) spectroscopy (Figure S3) revealed that their characteristic absorption peaks are almost the same except for the infrared absorption peaks in the fingerprint region, which is different from our report. This may be the reason for the different morphologies of the CoFe-SUCS and Co-CDSAAs.…”
Section: Resultscontrasting
confidence: 82%
See 1 more Smart Citation
“…When the reaction was extended to 3–6 h, the CoFe-SUCS structure remained almost the same morphology of the sea urchin-like hollow core–shell nanosphere, which is completely different from that of Co-CDSAAs (Figures f–i and S2f–i). Fourier transform infrared (FT-IR) spectroscopy (Figure S3) revealed that their characteristic absorption peaks are almost the same except for the infrared absorption peaks in the fingerprint region, which is different from our report. This may be the reason for the different morphologies of the CoFe-SUCS and Co-CDSAAs.…”
Section: Resultscontrasting
confidence: 82%
“…Considering these points, with the inspiration of our previous work, we report a strategy of cation exchange followed by Ar/H 2 annealing to construct a bird nest-like bimetallic OER electrocatalyst with a/c heterostructure nanosphere (BN-Fe 3 O 4 /CoO x ). In this design, cobalt coordination-driven self-assembled aggregates (Co-CDSAAs) are still the precursor as we used before .…”
Section: Introductionmentioning
confidence: 99%
“…The EIS serves as an effective indicator, offering insights into both the rate of electron transfer and the resistance between the electrode/electrolyte interfaces. 59 One of the key factors is charge transfer resistance ( R ct ), which reflects the kinetics of the electrocatalysts towards the OER activity. The 5 wt% Se–NiCo 2 O 4 /NiO electrocatalyst reveals 7.65 Ω charge transfer resistance, which is smallest in comparison with those obtained for 10 wt% Se–NiCo 2 O 4 /NiO (9.51 Ω), NiCo 2 O 4 /NiO (14.2 Ω), 5 wt% Se–NiCo–LDH (10.6 Ω), 10 wt% Se–NiCo–LDH (11.6 Ω) and NiCo–LDH (15.4 Ω).…”
Section: Resultsmentioning
confidence: 99%
“…The EIS serves as an effective indicator, offering insights into both the rate of electron transfer and the resistance between the electrode/electrolyte interfaces. 59 One of the key factors is charge transfer resistance (R ct ), which reflects the kinetics of the electrocatalysts towards the OER activity. These findings suggest a substantial improvement in the electrical conductivity of materials after the introduction of 5 wt% Se, leading to greater reaction kinetics.…”
Section: Electrocatalytic Oer Performancementioning
confidence: 99%
“…Notably, the surface of CoCuSe was reconstructed after OER, which transformed nanofiber to nanosheet. Based on previous studies, it is known that transition metal selenides are transformed into oxyhydroxide species, which are active species of OER, due to surface reconstruction during OER. ,,, The ratio of Cu 1+ and Cu 2+ (Cu 1+ /Cu 2+ ) was changed from 1.06 (before the OER) to 0.98 (after OER). Also, the ratios of Co 3+ and Co 2+ (Co 3+ /Co 2+ ) were 0.87 (before OER) and 1.85 (after OER), suggesting the formation of active oxyhydroxide species due to surface reconstruction after OER. ,, Interestingly, noticeable variations were observed in the XPS spectrum of O 1s …”
Section: Resultsmentioning
confidence: 99%